Clinical characteristics and related influencing factors of common rheumatic diseases concomitant with tuberculosis - Tang, Guo; Chen, Xixi; Han, Yaxin; Peng, Qing; Liu, Jiajun; Liu, Yan; Guo, Hongmei; Wu, Xiaodan; Liu, Jian; Zhou, Qiao; Long, Li (Frontiers in Public Health, 2023)
Objective: To explore the clinical characteristics and risk factors of common systemic rheumatism concomitant with tuberculosis (TB). Methods: A total of 3,906 patients of RA, SLE, and SS diagnosed in the People's Hospital of Sichuan Province from January 2007 to January 2017 were collected. One hundred and five patients with TB were included as TB group, including 42 RA, 41 SLE, and 22 SS patients. In the non-TB group, 84 RA, 82 SLE, and 44 SS patients were randomly selected during the same period. Results: Fever was the most common symptom among RA, SLE, and SS patients with TB, accounting for 83.3%, 92.7%, and 68.2%, respectively. Cough, weight loss or fatigue were the next common. RA patients with TB were mostly pulmonary TB (PTB), accounting for 64.3%. The proportion of PTB for SLE and SS were 46.3%, 59.01%, respectively. In TB group, 59% RA, 57% SLE, and 62% SS with PTB had two or more chest CT findings. There were 48 TB cases received both Interferon Gamma Release Assay (IGRA）and Tuberculin skin test (TST ) with positive rates of 91.8%,45.8% respectively. The daily average dose of glucocorticoids within 1 year in TB group was higher than that in non-TB group of SLE patients, lower counts of CD4+ T cell count were found in TB group (P<0.05), while no such differences were found in RA and SS patients. Conclusion: RA patients with TB are mainly pulmonary TB. For SLE and SS patients, the chance of PTB and extrapulmonary tuberculosis is similar. Daily average dose of glucocorticoids within 1 year may be a common risk factor for RA, SLE and SS patients developing TB. Decreased CD4+ T cell count may also be a risk factor for SLE patients with TB. Symptoms of RA, SLE, SS with TB, are similar with the primary disease or other infection. It is recommended to conduct both TST and IGRA to help diagnose TB.